The Connection between Algebraic Ability and Self-Efficacy in Senior High School Student - Firmanti, Pipit; Reflina, Reflina (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2022)
Algebra is important to learn as a provision in the face of future life, both at work and as preparation for higher education. However, basically students still have difficulty in solving algebra problems. Therefore, it is necessary to find out the factors that cause students' low algebraic abilities.The purpose of this study is to find the relationship between the algebraic abilities of students at Senior High School with their self-efficacy. The research is qualitative and quantitative. Statistic descriptive is to determine the connection and contribution of two variables, students' self-efficacy, and algebraic abilities. The research subjects taken were 200 students from Bukittinggi (West Sumatra). In this study, there were two instruments used, namely a self-efficacy questionnaire and an algebra test (SPLTV linear programming). The result shows that (1) In general, students' algebraic abilities are at a medium level with an average of 53.87. (2) Between algebraic abilities and self-efficacy have a very weak or very low correlation, so the correlation is ignored (it is assumed that there is no correlation between students' algebraic skills and self-efficacy) (3) Almost all students have good self-efficacy which is at a very high and quite low level. The finding implies that it is necessary to conduct research on the discovery of other factors that affect students' algebraic abilities.Aljabar penting dipelajari sebagai bekal dalam menghadapi kehidupan masa depan, baik di tempat kerja maupun sebagai persiapan menuju pendidikan tinggi. Namun, pada dasarnya siswa masih kesulitan dalam menyelesaikan soal aljabar. Oleh karena itu, perlu di cari tahu faktor penyebab kemampuan aljabar siswa yang masih rendah. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara kemampuan aljabar siswa SMA Negeri Bukittinggi dengan efikasi diri siswa. Penelitian ini merupakan gabungan antara kualitatif dan kuantitatif. Deskriptif statistik untuk mengetahui hubungan dan kontribusi dua variabel yaitu efikasi diri dan kemampuan aljabar siswa. Subjek penelitian yang diambil adalah 200 siswa dari Bukittinggi (Sumatera Barat). Dalam penelitian ini terdapat dua instrumen yang menggunakan angket efikasi diri dan tes aljabar (SPLTV Program linear). Hasil penelitian menunjukkan bahwa (1) Secara umum kemampuan aljabar siswa berada pada taraf sedang dengan rata-rata 66,125. (2) Antara kemampuan aljabar dan efikasi diri memiliki korelasi yang sangat lemah atau sangat rendah, sehingga korelasi tersebut diabaikan (diasumsikan tidak ada hubungan antara kemampuan aljabar siswa dengan efikasi diri) (3) Hampir semua siswa memiliki efikasi diri yang baik berada pada tingkat yang sangat tinggi dan cukup rendah. Penelitian ini menunjukkan bahwa perlu dilakukan penelitian lebih lanjut tentang faktor lain yang mempengaruhi kemampuan aljabar siswa.